2012
DOI: 10.1080/08964289.2011.651174
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Antihypertensive Adherence: A Feasibility Study on the Use of Student Health Coaches for Uninsured Hypertensive Adults

Abstract: Background Despite pharmacologic advances, medication non-adherence continues to challenge primary care providers in blood pressure (BP) management. Methods Medical, nursing and pharmacy students (n = 11) were recruited and trained as health coaches for uninsured, hypertensive patients (n = 25) of a free clinic in an uncontrolled open trial. Pre-post analysis was conducted on BP, medication adherence, frequency of home BP monitoring, and healthy behavior (e.g., diet, exercise). Patient satisfaction and feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 20 publications
0
44
0
2
Order By: Relevance
“…At the least intensive end, only 1.5 hours of training were provided to content experts in weight loss and consisted of the rationale for health coaching 62 or 2 hours of coaching-specific training were provided to MD, PharmD, or RN student health coaches to support uninsured patients with hypertension. 63 At the most intensive end, a 9-month curriculum was provided to medical assistants to coach patients with chronic health issues, 64 and an estimated 600 hours of training were provided to non-medical professionals to help newly diagnosed cancer patients navigate the healthcare system and their treatment. Greater than 6 wk (eg, 1 y experience plus CDE training, 600 h, ICF certification required) 5…”
Section: Training Received By the Coachesmentioning
confidence: 99%
“…At the least intensive end, only 1.5 hours of training were provided to content experts in weight loss and consisted of the rationale for health coaching 62 or 2 hours of coaching-specific training were provided to MD, PharmD, or RN student health coaches to support uninsured patients with hypertension. 63 At the most intensive end, a 9-month curriculum was provided to medical assistants to coach patients with chronic health issues, 64 and an estimated 600 hours of training were provided to non-medical professionals to help newly diagnosed cancer patients navigate the healthcare system and their treatment. Greater than 6 wk (eg, 1 y experience plus CDE training, 600 h, ICF certification required) 5…”
Section: Training Received By the Coachesmentioning
confidence: 99%
“…Twenty-four studies were cross-sectional [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and others were cohort, [35] observational, [36] and interventional studies. [32] Only 1 randomized controlled trial (RCT) was found. [29] The sample size of studies ranged from 25 [32] to 2445 [21] subjects.…”
Section: Characteristics Of Studies Assessedmentioning
confidence: 99%
“…Nine of the studies were conducted in the United States, [11,12,15,26,29,30,32,33,35] and 2 each in China, [11,17] Nigeria, [16,22] Hong Kong, [21,25] and Iran. [10,18] Countries such as Uganda, Lebanon, Kenya, Republic of Korea, Peru, Ethiopia, Ghana, Malaysia, Palestine, Brazil, and Italy were represented with a single study.…”
Section: Characteristics Of Studies Assessedmentioning
confidence: 99%
See 2 more Smart Citations